Optical properties of copper helical nanostructures: the effect of thickness on the SPR peak position. (20th August 2022) - Potočnik, J; Božinović, N; Novaković, M; Barudžija, T; Nenadović, M; Popović, M
Abstract: In this study, we have investigated the effect of thickness on the structural and optical properties of copper (Cu) helical nanostructures. Thin films with thicknesses of 160 nm, 280 nm, 450 nm, and 780 nm were obtained by e-beam glancing angle deposition. The morphology and the microstructure were studied by field emission scanning electron microscopy, x-ray diffraction and transmission electron microscopy, while for the optical analysis measurements spectroscopic ellipsometry was used. The results show that the deposited structures are porous with nanometer-sized crystallites preferentially oriented along (111) planes, as well as that the diameter of the helices increases with thickness. Detailed analyses of optical properties have demonstrated that the dielectric function of Cu structures is greatly influenced by the films thicknesses. With increasing thickness from 160 nm to 780 nm, the surface plasmon resonance peak was shifted from 1.31 eV to 1.05 eV, which was correlated with the growth mechanism and the size of deposited nanostructures.